Penerapan Teknologi Eco-Effisiensi Dan Green Economy Dalam Upaya Menuju UKM Tahu Mandiri Energi Di Kelurahan Margoagung, Kepenawon Seyegan Kabupaten Sleman - Rahayu, Suparni Setyowati; Nansi, Maria Regina; Arbintarso, Ellyawan S (Journal of Dedicators Community, 2022)
The Community Partnership Program at the Khale Tahu Sehat UKM in Margoagung Village, Kapanewon Seyegan, Sleman Regency aims to realize the role of IST AKPRIND Yogyakarta with the output of a superior research strategy plan on renewable energy and environmental engineering in a more real way in partner SMEs. One of the home industry clusters that has received a lot of attention from an environmental perspective is the small tofu industry located in the Margoagung Village. The rapid development of the small tofu industry will have a positive impact on progress that brings an increase in the economic income of rural communities. However, the waste generated from the tofu production process will have a negative impact on the village environment, becoming smelly and dirty. Based on these negative impacts, tofu waste water from small industries in rural areas has the potential to pollute the environment if it is disposed of directly without any treatment. Soil pollution can occur when wastewater seeps into the ground and can result in resident wells close to the seepage of the wastewater that cannot be used anymore. Therefore, it is necessary to develop technology for wastewater treatment that can produce biogas as renewable energy that can be developed so that it is beneficial for the community rural population (eco-efficiency technology). The use of this waste management method is not only "handling" but also has use/benefit as renewable energy and the liquid waste that comes out of the digester is used for agricultural irrigation and the sludge is used organic fertilizer, therefore saving on water, materials and energy is needed. This technology can reduce pollutant solids in the range of 75-90%. The method used in the implementation of the Tofu UKM development program is by socialization, the application of technology with the anaerobic method, eco-efficiency technology, easy to practice with relatively cheap and easy-to-obtain equipment so that small and medium industry players no longer assume that small and medium industry wastewater treatment is a very expensive load. In addition, alternative methods of waste treatment with economic value are sought that can produce biogas as renewable energy for fuel for grinding machines, and soy-boiling boilers. Meanwhile, the methods used are socialization, training, equipment manufacturing, application of technology based on Enterprise Resource Planning (ERP) and marketing IT, as well as assistance to solve the liquid waste problem of small tofu industries in an effort to realize a Green Economy. UKM Tahu Sehat Khale expands the market network with the IT e-commerce method, which can increase by 40%. The results obtained are appropriate technological equipment to increase production by 40%, including 1 (one) vertical soybean grinding machine, 1 (one) horizontal soybean grinding machine, 1 (one) unit boiling boiler, 10 m3 volume anaerobic digester 1 (one) unit. one) unit, 1 (one) ERP-based IT e-commerce device, 2 (two) e-commerce accounts, turnover and assets increased by 40% in addition to publications through the mass media of National newspapers, 1 (one) video, 1 (one) ) articles in ISSN journals, 1 (one) article in national proceedings and 1 (one) article in international conferences, 3 (three) Copyrights, 10 MBKM students build villages that are recognized for 10 credits in one year of program implementation.Â